Anti-mobilization activities of armed resistance movement (part 1) - Oleksandr Kuryliak (Cхід, 2018)
The article examines and analyzes the counteractions to the mobilization of Western Ukraine male citizens to Red Army by Organization of Ukrainian Nationalists and Ukrainian Insurgent Armyfrom 1944 to 1945. It was found out that to prevent military recruitment, underground and insurgent organizations conducted an anti-mobilization propaganda campaign, which included the production and distribution of corresponding leaflets (only anti-mobilization and the ones, containing anti-mobilization appeals), holding the anti-mobilizations meetings, and spreading gossip. As a mean of military recruitment opposition, insurgents were also destroying or stealing the mobilization documents (i.e., the lists of people liable for the call-up, notice papers, recruitment office orders), which were held in village Soviets.